The Impact of Population, Export, and Capital Formation to The Oil Consumption and Economic Growth in Indonesia - Farabi Ahmad; Aminu Zubairu Surajo (Economics, Business, Accounting & Society Review, 2022)
The paper aims to investigate the relationship between oil consumption and economic growth by including several variables namely capital, population and export in Indonesia using annual data for the period 1965 – 2021. Granger causality employed to determine the direction of causal relationship between the variables where the result can illustrate the ability of the country in reducing the energy consumption and the impact on economic growth. The study note the variable are stationer at first difference and two cointegration exists between the variables. In the short-run, capital has positive influence oil consumption for one and two lag. GDP and export negatively influence to oil consumption with maximum 2 lag period. In the long-run, capital and export oppositely influence oil consumption. The result of Granger causality supports the presence of conservation hypothesis between GDP and oil, GDP and export as well as GDP and capital. Feedback hypothesis confirms between oil consumption and export and oil consumption and population. The neutrality hypothesis exists between capital and oil consumption. Therefore, it can be concluded that the economic growth of Indonesia does not depend on the level of oil consumption. It implies that Indonesia government may impose energy conservation policy particularly oil without fear of negatively affecting economic growth.